Effectiveness of Problem-based Research Skill Development Flipped-classroom E-module for Critical Thinking and Scientific Literacy - Siregar, Nirmala Santy; Paidi, Paidi (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aims to evaluate the effectiveness of a Problem-based Learning (PBL) e-module integrated with Research Skill Development (RSD) and implemented through a flipped classroom approach to enhance students’ critical thinking skills and scientific literacy. The research employed a quasi-experimental design with a non-equivalent control group. The implementation was carried out at a state senior high school in Yogyakarta, involving 65 students, with 30 assigned to the control group and 35 to the experimental group. Data collection instruments included observation sheets for learning implementation and validated tests measuring critical thinking skills and scientific literacy. The data were analyzed using descriptive statistics (mean and percentage) and inferential statistics through bootstrap MANOVA followed by bootstrap ANOVA. The MANOVA analysis yielded a significance value (p < 0.001), indicating that the PBL-RSD e-module effectively improved both critical thinking skills and scientific literacy simultaneously. Furthermore, the bootstrap ANOVA results showed that the PBL-RSD e-module had a stronger impact on scientific literacy (57%) compared to critical thinking skills (27%). This difference is attributed to the PBL-RSD e-module’s deliberate focus on information exploration, data management, and interpretation, which are the key indicators in scientific literacy. These findings suggest that the PBL-RSD e-module, implemented through a flipped classroom model, can serve as an alternative instructional resource to develop students’ critical thinking and scientific literacy in biology learning.